b - Hall, Kathy; Burke, Winifred M. (b, 2010)
Drawing on case studies from primary classrooms, this book analyzes how teachers use formative assessment to promote learning. Themes addressed include feedback; power and roles of learners and teachers; self-assessment and peer assessment; and sharing success criteria with learners. The book equips teachers, student teachers, educators, and researchers with a sophisticated grasp of issues in formative assessment and how they relate to the promotion of pupil learning
Includes bibliographical references and index.
Keywords: Educational tests and measurements; Elementary school teaching